Risk Factors for Surgical Site Infection Following Cesarean Delivery - Syeda Rabia Bukhari, Momy Gul, Umber Asad, Lamia Yusuf, Surraya Israr, Abiha Khurrum, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Obstetrics' most common surgery is the cesarean section. The most common cause of hospitalization is surgical site infection, which increases morbidity and mortality. Postpartum infection is most commonly caused by cesarean section. The present study aimed to determine the several risk factors for surgical site infections after caesarean birth. Patients and Methods: This case-control study was conducted on 874 women underwent cesarean section in the department of Obstetrics and Gynecology at Moulvi Ameer Shah Memorial Hospital, Peshawar from January 2022 to September 2022. Patients were categorized into study group and control. A case is a patient who developed surgical site infections (SSI) after undergoing cesarean section surgery, while a control is a patient who had the procedure before or after SSI wasn't developed. Using the bivariate and multivariate logistic regression methods, infections on the patients were detected based on physical examination, laboratory reports, and post-operative follow-ups. Data analysis was done in SPSS version 28. Results: Of the total 874 cesarean cases, the prevalence of surgical site infection after cesarean section was 84 (9.6%). The age wise distribution of cases with SSI were as follows: 12 (14.3%) in 15-25 years, 62 (73.8%) in 26-35 years, and 7 (8.3%) in >35 years. Among 84 cases, the incidence of superficial type and deep incisional type was 80 (95.2%) and 4 (4.8%) respectively. The incidence of SSI diagnosis within 10 and after 10 postoperative days were 57 (67.9%) and 27 (32.1%) respectively. Among SSI diagnosed cases, the prevalence of normal, overweight, and obese patients were 16 (19%), 40 (47.7%), and 28 (33.3%) respectively. The prevalence of primipara was 72% (n=60) in SSI group. Out of total SSI cases, the incidence of primary and repeated CS was 74 (88.1%) and 10 (11.9%) respectively. In the SSI group, 45.2% (n = 38) out of total cases had medical complications like hypertension, diabetes, anemia, hypothyroidism, autoimmune diseases like scleroderma and SLE, and fever. Conclusion: The present study concluded that the prevalence of surgical site infection after cesarean section was 9.6%. The chances of surgical site infection after cesarean section increase as one gets older, obese, suffers medical complications while pregnant, goes into labor during a cesarean section, and has more than five PV examinations. Obstetricians should take precautions to avoid preventable risk factors. Keywords: Surgical site infection, Risk factors, Cesarean section